Effect of Step Geometry on Local Scour Downstream of Stepped Chutes - Tuna, M. Cihat; Emiroglu, M. Emin (Springer Heidelberg, 2013)
A chute is characterized by a steep bed slope associated with torrential flow. The chute flow may be either smooth or stepped. Stepped spillways (or chutes) have become a popular method for handling flood releases. Scour hole formed downstream of a chute may affect the safety and stability of the hydraulic structure. In this study, the effect of step geometry on the dynamics of local scour processes is analyzed in the context of the scour that takes place downstream from a stepped chute. Three different step heights have been used to study the scour process for various chute angles, stilling basin sill heights, tailwater depths and flow rate conditions. A total of 216 laboratory tests have been conducted and the findings have been analyzed to determine the influence of step geometry on the scouring at the downstream of the stepped chute. The results show that the equilibrium depth of scour is highly dependent on the step geometry. In addition, the equilibrium depth of scour decreases while the step height increases. Also, the equilibrium depth of scour also increases with an increase in the discharge and the chute angle.
Keywords: Stepped spillway; Chute; Scour; Energy dissipation